2021
DOI: 10.1167/jov.21.8.11
|View full text |Cite
|
Sign up to set email alerts
|

Icy road ahead—rapid adjustments of gaze–gait interactions during perturbed naturalistic walking

Abstract: Most humans can walk effortlessly across uniform terrain even when they do not pay much attention to it. However, most natural terrain is far from uniform, and we need visual information to maintain stable gait. Recent advances in mobile eye-tracking technology have made it possible to study, in natural environments, how terrain affects gaze and thus the sampling of visual information. However, natural environments provide only limited experimental control, and some conditions cannot safely be tested. Typical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(38 citation statements)
references
References 61 publications
9
28
1
Order By: Relevance
“…All participants reported being sufficiently rested and focused in a questionnaire prior to the experiment, were naïve to the hypotheses and debriefed after the experiment. We aimed for a power of 80 % (Cohen, 1988) which, given 𝛼 = .05 and Cohen's 𝑓 = 0.25 (a realistic estimate based on previous work, Kopiske et al, 2021), required a sample size of 𝑁 = 24. A total of 27 participated, as after inspecting data quality, but prior to any hypothesis-related analysis, data of three participants had to be excluded due to a high proportion of missing eyetracking data (>20 % missing values, same cut-off as used in Kopiske et al, 2021).…”
Section: Participantsmentioning
confidence: 99%
See 3 more Smart Citations
“…All participants reported being sufficiently rested and focused in a questionnaire prior to the experiment, were naïve to the hypotheses and debriefed after the experiment. We aimed for a power of 80 % (Cohen, 1988) which, given 𝛼 = .05 and Cohen's 𝑓 = 0.25 (a realistic estimate based on previous work, Kopiske et al, 2021), required a sample size of 𝑁 = 24. A total of 27 participated, as after inspecting data quality, but prior to any hypothesis-related analysis, data of three participants had to be excluded due to a high proportion of missing eyetracking data (>20 % missing values, same cut-off as used in Kopiske et al, 2021).…”
Section: Participantsmentioning
confidence: 99%
“…On each time scale, we analyzed eye, head, and body movements to look at persistent changes. Previously, we had shown that participants respond to such perturbations by adapting their gaze both directly and long-term, and differently depending on whether there were visual cues to give advance notice of the perturbation or not (Kopiske et al, 2021). If the adverse effects of increased cognitive load are not offset by a more cautious gait mode, one would predict a stronger reaction of gaze and gait parameters to the perturbation while performing a cognitive task than without secondary task.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Perry and colleagues (2020) found similar results during reaching, with fixation distance increasing as participant performance improved. During walking, healthy adults also look farther ahead as they practice and become more skilled at both obstacle avoidance (Kopiske et al 2021) and target stepping (Cates and Gordon 2022). This suggests that as people learn to perform a task, the role of vision shifts towards informing feedforward motor control strategies.…”
Section: Introductionmentioning
confidence: 99%